2012
DOI: 10.1371/journal.pone.0046066
|View full text |Cite
|
Sign up to set email alerts
|

Time Course Analysis of Motor Excitability in a Response Inhibition Task According to the Level of Hyperactivity and Impulsivity in Children with ADHD

Abstract: Short interval intracortical inhibition (SICI) of motor cortex, measured by transcranial magnetic stimulation (TMS) in a passive (resting) condition, has been suggested as a neurophysiological marker of hyperactivity in attention-deficit/hyperactivity disorder (ADHD). The aim of this study was to determine motor excitability in a go/nogo task at stages of response preparation, activation and suppression in children with ADHD, depending on the level of hyperactivity and impulsivity. Motor evoked potentials were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…In the second and third task block, a monetary reward (10 cents per trial) was given for fast responses in go‐trials to increase motivation. The time window, for which fast responses were rewarded, was based on a tracking algorithm and was dynamically adjusted to the 75th percentile of reaction times (go‐trials) of the previous block (Hoegl et al., ). The same amount of money was subtracted in the case of an incorrect reaction (reaction to a nogo trial or no reaction to a go‐stimulus).…”
Section: Methodsmentioning
confidence: 99%
“…In the second and third task block, a monetary reward (10 cents per trial) was given for fast responses in go‐trials to increase motivation. The time window, for which fast responses were rewarded, was based on a tracking algorithm and was dynamically adjusted to the 75th percentile of reaction times (go‐trials) of the previous block (Hoegl et al., ). The same amount of money was subtracted in the case of an incorrect reaction (reaction to a nogo trial or no reaction to a go‐stimulus).…”
Section: Methodsmentioning
confidence: 99%
“…SICI was selected as a primary candidate based on case-control studies showing reduced SICI in ADHD and correlations between less SICI and greater ADHD symptom severity. 7,10,16,20 Moreover, in prior studies, SICI did appear to be sensitive to single doses of psychostimulants and of norepinephrine reuptake inhibitors reboxetine and ATX. 6,8,16,31 Most single dose studies have recruited small samples of healthy adults or children.…”
Section: Discussionmentioning
confidence: 90%
“…Some groups have successfully used TMS during GNG task to show differences in cortical physiology in children and adults. 14,23,34 However, GNG task should ideally be conducted at a relatively fast pace to elicit prepotent motor response throughout the task so that inhibitory control can be adequately examined in Nogo trials. 35,36 From methodological standpoint, a fast-paced GNG task imposes difficulties for online fTMS experiments as device capacitors require time to recharge for the next stimulation pulse.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one study showed that a single dose of methylphenidate changed motor cortical physiology of healthy adults during an fTMS/GNG experiment. 22 To date, there are two groups that have published pediatric fTMS studies using GNG task to characterize cortical physiology of ADHD 23 and Tourette Syndrome 17 . There is currently no published fTMS study utilizing SST in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%